2022
DOI: 10.1101/2022.01.29.22269933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-demographic characteristics and their relation to medical service consumption among elderly in Israel during the COVID-19 lockdown in 2020 compared to the corresponding period in 2019

Abstract: Purpose: The COVID-19 pandemic has led to the isolation of the population in Israel, including the elderly, some of whom are chronically ill. The present study examines the consumption of medical services among adults over the age of 65 in Israel at the time of the first COVID-19 lockdown relative to the corresponding period the year before, according to various socio-demographic variables: gender, age, marital status, ethnicity, degree of religiosity and socioeconomic status. Methods: A retrospective longitud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Regarding differences between types of housing, a few studies found that isolation was particularly difficult in crowded apartments inhabited by low-income individuals, including older adults and those most susceptible to infection. As a result, limited living space contributed to the exacerbation of disease and mental disorders, mainly due to overcrowding [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding differences between types of housing, a few studies found that isolation was particularly difficult in crowded apartments inhabited by low-income individuals, including older adults and those most susceptible to infection. As a result, limited living space contributed to the exacerbation of disease and mental disorders, mainly due to overcrowding [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%